Inflation Targeting in Emerging Economies: the Assessment of the Polish Experience (1995-2015) - Poutineau, Jean-Christophe; Vermandel, Gauthier (DEMO, 2017)
The aim of this paper is to assess the Polish monetary policy experience between 1995Q1 and 2014Q4 in the light of the three equation new Keynesian model estimated with Bayesian econometrics. Our results show that the National Bank of Poland has performed relatively well in stabilizing activity and infl ation as the results observed are very close to the ones obtained under either an aggressive simple interest rule.(original abstract)
Keywords: Monetary policy; NBP monetary policy; State monetary policy; Dynamic Stochastic General Equilibrium (DSGE); Bayesian models; Taylor rule